2013
DOI: 10.1371/journal.pone.0078245
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression of Desaturase (FADS1 and FADS2) and Elongase (ELOVL5) Enzymes in Peripheral Blood: Association with Polyunsaturated Fatty Acid Levels and Atopic Eczema in 4-Year-Old Children

Abstract: BackgroundIt is unknown if changes in the gene expression of the desaturase and elongase enzymes are associated with abnormal n-6 long chain polyunsaturated fatty acid (LC-PUFA) levels in children with atopic eczema (AE). We analyzed whether mRNA-expression of genes encoding key enzymes of LC-PUFA synthesis (FADS1, FADS2 and ELOVL5) is associated with circulating LC-PUFA levels and risk of AE in 4-year-old children.MethodsAE (n=20) and non-AE (n=104) children participating in the Sabadell cohort within the INf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…Genes with a H2H orientation are prone to co-expression and co-functionality33. Disturbed expression of the FADS genes has previously been reported in several IgE-mediated diseases, including asthma34 and atopic dermatitis3536, but this is the first such association with the direct cellular processes leading to IgE production. Variation in FADS gene expression during the activation time course is shown in supplementary Figure S3.…”
Section: Resultsmentioning
confidence: 85%
“…Genes with a H2H orientation are prone to co-expression and co-functionality33. Disturbed expression of the FADS genes has previously been reported in several IgE-mediated diseases, including asthma34 and atopic dermatitis3536, but this is the first such association with the direct cellular processes leading to IgE production. Variation in FADS gene expression during the activation time course is shown in supplementary Figure S3.…”
Section: Resultsmentioning
confidence: 85%
“…Likewise, genetic modulation by sex may be another relevant factor explaining some differences in the effect of the genetics of PUFA. Some PUFA are specifically required for reproduction [104]. It has been reported that PUFA concentrations are higher in females than in males during pregnancy and there are some studies showing sex-specific effects for some PUFA in determining several outcomes [68][69][70][71][72][73][74]140,141].…”
Section: Discussionmentioning
confidence: 99%
“…In Spain, the adherence to the Mediterranean diet pattern [99] is still relatively high in older subjects, but is decreasing in young people [100,101]. Although some studies specifically carried out in the Spanish Mediterranean population, have analyzed the association between several FADS and ELOVL candidate gene polymorphisms and PUFA concentrations [102][103][104][105][106], no study has investigated such associations at the GWAS level.…”
Section: Introductionmentioning
confidence: 99%
“…This analysis also uncovers the pattern that odd-chain fatty acid residues are more abundant in the hearts of lean mice. These results are interpretable in terms of the aetiology of metabolic and heart disease [24,[41][42][43][44] in a manner that is orthogonal to the abundance analysis of whole lipids.…”
Section: Lipidome Analysismentioning
confidence: 99%